Stellarioides exigua (Asparagaceae, Scilloideae), a new species from South Africa - Martínez-Azorín, Mario; Crespo, Manuel B.; Dold, Anthony P.; Pinter, Michael; Wetschnig, Wolfgang (Phytotaxa, 2015)
Within the framework of a taxonomic revision of the genus Stellarioides we here describe a new species from South Africa, Stellarioides exigua. This taxon is, at first sight, related to S. arida and S. tenuifolia s.l., but it can be clearly differentiated by the small general size; the filiform, free leaves; the small narrowly lanceolate capsules and the small seeds. A complete description of the species is presented, and data on morphology, ecology, and distribution are reported. Affinities and divergences with other taxonomically closely related taxa are also discussed.